Desvelando as teias de Pinóquio :concepções de família em jovens moradores de bairros periféricos - Nascimento, Périsson Dantas do (2003)
This thesis discusses family as a social and historical construction and concerns to the perceptions developed by the peripheral youth living in suburbs. It investigates the speeches of young boys and girls who take part in Engenho de sonhos a forum composed by a pool of eleven non-governmental organizations and UFRN which aim is the elaboration and execution of projects focusing local development of poor communities in violence and social exclusion context. Throughout interactive diagnosis seminars in five communities in West Side of Natal with six hundred teenagers, it was detected the need to work with family relationships. In order to build the methodological corpus a range variety of procedures were done such as: interviews, focal groups and psychosocial questionnaires with nine local young leaders. The purpose to understand data guided the research through the theory of social imagery and pointed out the following themes: conceptions, relationship, roles, family projects. Live stories of these young population reveals conflicts when it comes to the configuration of family ties, far from the family model stated by society. Family is also, in their perception, an important space to the development of affection, in experiences of all sorts, affecting personality development and determining behaviors in local contexts. The research concludes stating the urge to comprehend this academic work as a way to fight against symbolic and emotional poverty in family context producing discussions and critical reflection in a permanent relation between juvenile social vulnerability (characterized by lacks of all orders) and potential